Maternal prenatal stress and placental gene expression of NR3C1 and HSD11B2: The effects of maternal ethnicity. (January 2018) - Capron, Lauren E.; Ramchandani, Paul G.; Glover, Vivette
Highlights: Prenatal stress (maternal symptoms of depression, anxiety and life events) was associated with altered placental expression of HPA-axis genes. There was a significant interaction with ethnicity. There was increased placental NR3C1 and decreased HSD2B11 expression in Caucasians but no change in non-Caucasians. Further research is needed to examine the potential effects of ethnicity on the association between prenatal stress & placental gene expression. Summary: Background: Prenatal stress is associated with altered fetal and infant development. Previous studies have suggested that these effects may be mediated in part via altered functioning of placental enzymes and receptors involved in the HPA-axis, including the glucocorticoid receptor ( NR3C1 ) and HSD11B2, the enzyme which metabolises cortisol. However, previous studies have not examined the potential ethnicity effects on these associations. This study aimed to characterise the association between maternal prenatal stress and placental genes expression and subsequently, any potential effect of maternal ethnicity. Method: Pregnant women(n = 83) were recruited prior to elective caesarean section and assessed for trait anxiety, depression and life events. Placentas were collected and placental gene expression of NR3C1 and HSD11B2 were analysed. We examined associations between maternal prenatal stress and placental gene expression, and the tested for a possible moderating effect of maternal ethnicity(59.0% Caucasian;41.0% non-Caucasian:12.0% South Asian;6.0% African/African-American;14.4% Other;8.4% Mixed). Results: Analyses demonstrated a trend in the association between both maternal trait anxiety and depression symptoms with placental gene expression of NR3C1 (adj.β = 0.220, p = 0.067;adj.β = 0.212, p = 0.064 respectively). We found a significant interaction with maternal ethnicity(β = 0.249;p = 0.033). In Caucasian women only prenatal trait anxiety and depressive symptoms were associated with an increase in placental NR3C1 expression(adj.β = 0.389, p = 0.010;adj.β = 0.294;p = 0.047 respectively). Prenatal life events were associated with a down regulation of HSD11B2(adj.β = 0.381;p = 0.008), but only in Caucasians. Conclusion: These results support previous findings of an association between maternal prenatal stress and the expression of placental genes associated with the HPA-axis, but only in Caucasians. These ethnic specific findings are novel and require replication in different populations.